47.9k views
3 votes
Please help me with this question #20

Please help me with this question #20-example-1
User Doug Mead
by
5.9k points

1 Answer

3 votes

Answer:

answers C and D are both correct. (I consider D to be "simpler.")

Explanation:

By the rules of exponents ...

(a^b)^c = a^(b·c)

Here, we have a=-3, b=2. c=3, so ...

((-3)^2)^3 = (-3)^(2·3) = (-3)^6

___

Consider further that ...

-3 = (-1)(3)

and another rule of exponents tells you ...

(a·b)^c = (a^c)·(b^c)

so our previous simplified result can also be written as ...

(-3)^6 = ((-1)·(3))^6 = (-1)^6·(3)^6 = 1·(3)^6 = (3)^6

_____

I find it hard to tell just how "simplified" your answer key may want the answer to be. Of course, the simplest possible form is 729.

User Noah Lavine
by
5.7k points